(untitled) (Nigerian Dental Journal, 2009)
Ameloblastic carcinoma (AC) produces extensive local destruction, perforation of the cortical plate, extension into surrounding soft tissues, numerous recurrent lesions, and metastasis, usually to cervical lymph nodes. Clear cell odontogenic carcinoma (CCOC) which was previously designated clear cell odontogenic tumor also exhibits an aggressive biologic behavior and a tendency to metastasize to distant locations. Both lesions are rare. We report an odontogenic carcinoma with a dual histomorphologic feature of CCOC and AC coexisting in a single lesion. To the best of our knowledge, this is the first report of its kind in the literature.